From Dichotomy to Applied Islamization: Transforming the Relationship Between Islamic Education and Science in Indonesia - Soibatul Aslamiah Nasution; Wedra Aprison; Novi Susanti; Yulda Dina Septiana (Islamic Review: Jurnal Riset dan Kajian Keislaman, 2026)
This study is motivated by the limited research on contemporary policy implementation data regarding scientific transformation, despite its significant impact on the social legitimacy and global competitiveness of Islamic Higher Education Institutions (PTKIN) in Indonesia. The study aims to comprehensively analyze the conceptual evolution from Dichotomy to the applied Islamization of Knowledge phase and map its implementation through PTKIN strategic policies from 2020 to 2025. The research adopts a qualitative library research design, using an analytical comparative approach to evaluate official policy documents, curriculum reports (RPS), and accredited literature. Data was collected using systematic literature review and analyzed through qualitative interactive analysis, including data reduction, display, and conclusion drawing. The findings reveal that the Integrative-Interconnective Paradigm has successfully become the dominant philosophical framework, manifested through the Ministry of Religious Affairs' strategic emphasis on STEM-based research, ecotheology, and international collaborations. The study concludes that scientific transformation has reached a phase of applied Islamization where PTKIN acts as a producer of globally relevant knowledge. Implications include practical recommendations for stakeholders to standardize interconnective pedagogy and invest in faculty capacity building